Social Distancing and Stigma: Association Between Compliance With Behavioral Recommendations, Risk Perception, and Stigmatizing Attitudes During the COVID-19 Outbreak - Tomczyk, Samuel; Rahn, Maxi; Schmidt, Silke (Frontiers in Psychology, 2020)
Introduction. Following behavioral recommendations is key to successful containment of the COVID-19 pandemic. Therefore, it is important to identify causes and patterns of noncompliance in the population to further optimize risk and health communication. Methods. 157 participants (80% female; mean age= 27.82 (SD=11.01)) were surveyed regarding their intention to comply with behavioral recommendations issued by the German government. Latent class analysis examined patterns of compliance and subsequent multinomial logistic regression models tested sociodemographic (age, gender, country of origin, level of education, region, and number of persons per household), and psychosocial (knowledge about preventive behaviors, risk perception, stigmatizing attitudes) predictors. Results. Three latent classes were identified: high compliance (25%) with all recommendations, public compliance (51%), with high compliance regarding public but not personal behaviors, and low compliance (24%) with most recommendations. Compared to high compliance, low compliance was associated with male gender (RRR=0.08; [0.01; 0.85]), younger age (RRR=0.72; [0.57; 0.93]), and lower public stigma (RRR=0.21; [0.05; 0.88]). Low compliers were also younger than public compliers (RRR=0.76; [0.59; 0.98]). Discussion. With 25% of the sample reporting full compliance, and 51% differing in terms of public and personal compliance, these findings challenge the sustainability of strict regulatory measures. Moreover, young males were most likely to express low compliance, stressing the need for selective health promotion efforts. Finally, the positive association between public stigma and compliance points to potential othering effects of stigma during a pandemic, but further longitudinal research is required to examine its impact on health and social processes throughout the pandemic.